An estimate of spatial wage curve for Brazilian northeast region - Uchôa, Carlos Frederico A. (Nexos Econômicos, 2020)
The chief goal of this paper is to provide an investigation of the Wage Curve spatial heterogeneity for Brazilian northeast labor market. To do so, using the Wage Curve as Theoretical Framework, we apply spatial panel data techniques to compiled data set of 1,793 municipalities over 13 years from RAIS data to obtain the estimates of interest. Our results allow us to conclude there is a statistically significant negative correlation between unemployment and real wage as also that there are statistically significant effects on wages. In addition to confirm our initial assumption of existence of a Wage Curve, our finds also provide estimates that at least control spatial heterogeneity.